2000
DOI: 10.1159/000014239
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Fetal Growth Variability

Abstract: The aim of this study was to assess the variability in individual fetal growth rhythms in comparison to averaged standard curves obtained from cross-sectional data. Biparietal diameter (BDP), abdominal transverse diameter (ATD) and femur length (FL) were measured by ultrasonography in 24 normal subjects, and the variance in growth rates determined for four time intervals: 12–26, 26–34, 34–37 and 37–39 weeks gestation. BPD, ATD and FL growths were always linear until 26 weeks with low variances in growth rates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 5 publications
2
7
0
2
Order By: Relevance
“…This is in agreement with Owen et al who reported that growth velocity of the head was not significantly different from the reference population whereas the trunk growth velocity was significantly reduced in the third trimester in pregnancies with neonatal features of intrauterine malnourishment [11]. Previously, it has been reported that fetal measurements show linear growth rates until 26 weeks with low variances whereas growth rates related variances increase significantly thereafter with a great diversity in individual growth trajectories [25]. [8][9][10] week interval between US examination has been suggested as statistically reliable in assessing fetal growth [26].…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with Owen et al who reported that growth velocity of the head was not significantly different from the reference population whereas the trunk growth velocity was significantly reduced in the third trimester in pregnancies with neonatal features of intrauterine malnourishment [11]. Previously, it has been reported that fetal measurements show linear growth rates until 26 weeks with low variances whereas growth rates related variances increase significantly thereafter with a great diversity in individual growth trajectories [25]. [8][9][10] week interval between US examination has been suggested as statistically reliable in assessing fetal growth [26].…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, Guihard-Costa et al (7), on the basis of 24 pregnancies followed from the wk 7 up to delivery, asserts that differences in growth velocity emerge only during the third trimester. Whether possible differences in early intrauterine growth velocity are simply the effect of random growth fluctuations or, on the contrary, affect the size at birth is still a debated issue.…”
mentioning
confidence: 94%
“…In a previous study [3] , we attempted to determine the best model describing the kinetics of fetal head growth. We found a new two-phase mathematical model, computed independently for male and female data, taking into account the increasing inter-subject variability with gestational age, and the decrease in mean growth rate at about 30 gestational weeks, which has been reported previously [4] . The present study extends the previous model on two other dimensions usually involved in routine ultrasound screening of fetuses: the abdominal circumference (AC) and femur length (FL).…”
mentioning
confidence: 63%
“…The fi rst one was developed by Pineau [7] , and successfully tested on head circumference (HC) and biparietal diameter data [1] . Three other commonly used models were also computed: a linear-quadratic model (a + bt + ct 2 ), a linear-cubic model corresponding to the model used by Deter et al [8] to fi t longitudinal data (a + bt + ct 3 ) and the Rossavik equation [4] . To test the four models, we utilized the SYSTAT software to calculate the coeffi cient of determination (R 2 ) and the standard er- Fig.…”
Section: Mathematical and Statistical Analysismentioning
confidence: 99%